INCREASING THE COMPETITIVENESS OF HIGHER EDUCATION INSTITUTIONS BASED ON INNOVATIVE EDUCATIONAL PROJECTS (Marketing Journal, 2025)
This article analyzes the enhancement of higher education institutionsʼ competitiveness through the implementation of innovative educational projects . A strategic management approach based on a three -block model ( target , functional , and operational ) is proposed . The study explores opportunities for preparing universities for global competition via digital transformation , financial autonomy , marketing, and public -private partnerships . Recommendations are provided for building a sustainable innovation ecosystem through the integration of education , science , and industry .
Keywords: innovative education; competitiveness; strategic management; digital transformation; higher education; university governance; educational ecosystem; public -private partnership . 650